2015
DOI: 10.1007/s00405-015-3598-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective investigation of predictive parameters for post-surgical recurrences in sinonasal polyposis

Abstract: Even after appropriate surgical therapy, a significant number of patients with chronic rhinosinusitis with nasal polyps (CRSwNP) experience recurrences. The end-point of this prospective study was to apply univariate and multivariate statistical models to identify clinical, pathological, and laboratory variables that could predict CRSwNP recurrence after endoscopic sinus surgery. The study enrolled 143 patients between 2010 and 2013, who were all treated by the same surgeon for CRSwNP. Twenty-one patients deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 20 publications
0
26
1
Order By: Relevance
“…Recently, studies have found eosinophilia in nasal tissue and blood is closely related to surgical outcomes. 5,11,12 Tokunaga et al 13 created a model to classify CRS severity mainly based on blood eosinophil ratio in Japanese CRS patients. However, the degree of eosinophilia has significant geographic and ethnic differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies have found eosinophilia in nasal tissue and blood is closely related to surgical outcomes. 5,11,12 Tokunaga et al 13 created a model to classify CRS severity mainly based on blood eosinophil ratio in Japanese CRS patients. However, the degree of eosinophilia has significant geographic and ethnic differences.…”
Section: Introductionmentioning
confidence: 99%
“…15 Moreover, comorbid asthma and computed tomography (CT) scores are considered as risk factors in some studies, 7,13,16 but not in others. 9,17 In addition, researchers have demonstrated that age, 11 gender, 9 previous CRS surgery, 6,9 preoperative endoscopic score, 6 and allergy 11 are also related to poor ESS outcomes. Predictive models with these risk factors for clinical practice are needed.…”
Section: Introductionmentioning
confidence: 99%
“…The multivariate model presented that there was histological evidence between the eosinophilic type and the recurrence of nasal polyposis (p=0.033). 6 Olszewski et al stated that in their study they did 278 polipectomies, 6 months after FESS, by endoscopic examination there were patent paranasal sinuses ostiums, there were no inflammatory traits as swelling, redness of the nasal mucosa or any pathological secretion. There was adequate nasal patency in 93.7%, patients sensed of the blood flowing down to the mouth in 20.4%, mucorrhoea in 2.8%, impaired smell in 17.6% and headache in 2.8%.…”
Section: Resultsmentioning
confidence: 95%
“…Nasal inflammatory polyps are nonneoplastic proliferations of the sinonasal mucosa composed of both epithelial and stromal elements. The pathogenesis of these lesions is still uncertain; however, mucosal edema and inflammation, cytokine secretion, and collagen synthesis stimulated by eosinophils have all been implicated 1,2,3 ; polyps are frequently associated with salicylates intolerance, asthma and cystic fibrosis 1,2,3,4,5,6,7,8,9 . Symptoms at presentation include nasal obstruction, rhinorrhea, headache, impaired sense of smell and postnasal discharge 1,2,3,4,5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients who have failed medical management may benefit from surgical intervention in the form of transnasal ethmoidectomy or, more recently, functional endoscopic nasal surgery. Even after appropriate surgical therapy, a significant number of patients with chronic rhinosinusitis with nasal polyps (CRSwNP) experience recurrences 9 , with diseasefree interval significantly shorter in patients with eosinophilic-type polyposis. NP often present as multiple bilateral masses arising from the lateral nasal wall.…”
Section: Introductionmentioning
confidence: 99%